2021
DOI: 10.1042/cs20210753
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-induced REDD1 modulates Th17 cell responses that contribute to gastritis

Abstract: Objective: Regulated in development and DNA damage responses-1 (REDD1) is a conserved and ubiquitous protein, which is induced in response to multiple stimuli. However, the regulation, function and clinical relevance of REDD1 in Helicobacter pylori-associated gastritis are presently unknown. Approach: Immunohistochemistry, real-time PCR and Western blot analyses were performed to examine the levels of REDD1 in gastric samples from H. pylori-infected patients and mice. Gastric tissues from Redd1−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…There were remarkable associations between serum TNF-α and IL-8 levels and the degree of mucosa chronic inflammation in patients [37]. The Th17/ IL-17 immunoregulatory pathway is involved in H. pylori colonization and immune-inflammatory response [38]. The expression level of IL-17 was markedly elevated in the of H. pylori-infected individuals.…”
Section: Discussionmentioning
confidence: 94%
“…There were remarkable associations between serum TNF-α and IL-8 levels and the degree of mucosa chronic inflammation in patients [37]. The Th17/ IL-17 immunoregulatory pathway is involved in H. pylori colonization and immune-inflammatory response [38]. The expression level of IL-17 was markedly elevated in the of H. pylori-infected individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Mouse model studies have further revealed that this action of cagA intensifies gastritis progression in non-bone marrow-derived cells. Furthermore, cagA increases the expression of CXCL1, promoting the migration of MHC II+ mononuclear cells and the secretion of IL-23, which collectively lead to Th17 cell polarization and IL-17A production, exacerbating inflammation induced by H. pylori ( Yan et al., 2021 ). These findings deepen our understanding of cagA and its associated pathogenicity island (cagPAI) in the immune response elicited by H. pylori .…”
Section: Evasion Of Adaptive Immunitymentioning
confidence: 99%
“…The main reasons are heredity, constitution, immunity, diet and environment, Hp infection in the digestive tract, long-term use of drugs that stimulate the stomach (non-steroidal anti-inflammatory drugs, alcohol, etc.) and so on [ 20 , 21 , 22 , 23 ]. At present, it is found that Hp infection, diet, and environmental factors are the key factors that induce chronic gastritis.…”
Section: Etiological Analysis Of Cgmentioning
confidence: 99%